Needle-free injection enhancement of beef improves tenderness but slightly increases microbial translocation - Sutterfield, A.; Crow, B.A.; Grobbel, J.P.; Phebus, Randall K.; Dikeman, Michael E.; Hollis, Larry C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Blade tenderization has been used for decades to increase tenderness in beef cuts that are highly variable in tenderness or predicted to be “tough.” Injection enhancement also is commonly used in industry to increase tenderness, juiciness, and flavor of some beef muscles. These processes have the potential to translocate microbial organisms on the exterior to interior portions of whole muscles. One research study reported that 3 to 4% of surface bacteria are transferred into the interior of muscles but only penetrate an average of ¼ inch deep into the surface. Even though the frequency of subprimal surfaces being contaminated with pathogens is low, translocation of these contaminants into the interior of subprimals by tenderization or injection procedures poses a public health risk. Microbial contamination on beef surfaces generally is eliminated during typical cooking; however, given the low infectious doses of pathogens such as Escherichia coli O157:H7, internalized contamination may survive if adequate temperatures are not reached at the center of cuts (i.e., rare and medium rare endpoints) and lead to illness. Industry groups have developed a guide, Best Practices: Pathogen Control During Tenderizing/Enhancing of Whole Muscle Cuts to minimize any hazard that may be present with such technologies. Although needle injection enhancement currently is common in beef processing, there may be alternative, safer, or more effective means to apply these technologies. One potential method involves utilizing an air-pressured needle-free injection system similar to an instrument currently being investigated for use in vaccinating cattle. In theory, eliminating the need for physical penetration of the muscle with a needle-free instrument using air-pressure fluid streams would reduce the translocation of surface microbial contamination to the interior and would additionally minimize carryover contamination from subprimal to subprimal during continuous injection operations. Therefore, we investigated use of needle-free injection enhancement as an alternative strategy to needle injection enhancement. Our objectives were to determine the safety and efficacy of using needle-free injection for enhancing beef muscles and the application of needle-free injection enhancement for improving beef quality.
Keywords: Beef; Cattle; Needle-free injection; Tenderness